KOLABORASI LINTAS SEKTOR DAN TATA KELOLA AIR LIMBAH BERBASIS MULTI LEVEL GOVERNANCE DI KECAMATAN DRIYOREJO GRESIK - Irma Irfiyanti; Rachmawati Novaria; Hasan Ismail (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2026)
The problem of wastewater management in Gresik Regency reveals a gap between rising economic activity and effective environmental governance capacity. Low Water Quality Index data indicate that cross‑actor coordination has not yet significantly improved water quality. This study aims to analyse wastewater management in Driyorejo District through the Multi Level Governance framework by mapping actor roles and identifying the extent to which the four MLG indicators are reflected in practice. A qualitative descriptive approach was employed, using in‑depth interviews, observation, and documentation involving the Environmental Agency, sub‑district government, catering business actors, community members, and an environmental activist as a balancing informant. Data were analysed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, display, and conclusion drawing. The findings show that the four MLG indicators are formally present through role distribution, simple coordination, and daily waste management practices. However, evidence regarding supervisory effectiveness, system resilience under pressure, and direct impact on water quality improvement remains very limited. The harmonious narratives recorded have not revealed potential friction or power imbalances among actors. The study concludes that wastewater management at the research site exhibits an MLG framework at a surface level but cannot yet be claimed as an effective governance system. Its contribution lies in providing an initial actor map while emphasising the need for objective environmental performance measurement and power dynamics analysis in local‑level MLG research.